2009
DOI: 10.1590/s1807-59322009000800013
|View full text |Cite
|
Sign up to set email alerts
|

Comorbidities are Frequent in Patients with Gastroesophageal Reflux Disease in a Tertiary Health Care Hospital

Abstract: INTRODUCTIONSeveral aspects of gastroesophageal reflux disease (GERD) have been studied, but the frequency of comorbidities is not yet fully understood.OBJECTIVESTo study the prevalence of GERD comorbidities in a tertiary care hospital.METHODSWe prospectively studied 670 consecutive adult patients from the outpatient department of our facility. A diagnosis was established using clinical, endoscopic and/or pHmetry-related findings. Each patient’s medical file was reviewed with respect to the presence of other m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
12
1
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 25 publications
3
12
1
2
Order By: Relevance
“…This finding is in accordance with previous research [19]. Beyond this, our study provides additional documentation of disease clustering, indicating identifiable patterns linked to the selected index conditions gastro-esophageal reflux, thyroidal disease and dental/periodontal health, again in accordance with previous observations [50][51][52][53][54][55][56][57][58][59][60]. Our findings add to the accumulating documentation that patterns of morbidity are ubiquitous and transcend the biomedical dichotomies somatic/mental and organic/functional and also the diagnostic categories within the specialized medical domains.…”
Section: Discussionsupporting
confidence: 93%
“…This finding is in accordance with previous research [19]. Beyond this, our study provides additional documentation of disease clustering, indicating identifiable patterns linked to the selected index conditions gastro-esophageal reflux, thyroidal disease and dental/periodontal health, again in accordance with previous observations [50][51][52][53][54][55][56][57][58][59][60]. Our findings add to the accumulating documentation that patterns of morbidity are ubiquitous and transcend the biomedical dichotomies somatic/mental and organic/functional and also the diagnostic categories within the specialized medical domains.…”
Section: Discussionsupporting
confidence: 93%
“…In our study, prevalent comorbid diseases associated with GERD presence included hypertension, diabetes mellitus, dyslipidemia, congestive heart failure, and cerebrovascular as well as chronic pulmonary diseases, which is consistent with the results of previous studies with the exception of congestive heart failure [32][33][34][35]. No epidemiological studies have investigated the association between congestive heart failure and GERD.…”
Section: Discussionsupporting
confidence: 91%
“…This finding supports the previous study by Moraes-Filho JPP et al, who postulated the strong association of co-morbidities with GERD and its worsening effect on GERD. 12 Though heartburn, regurgitation and retrosternal chest pain are the classic presenting symptoms of GERD, in present study these symptoms were not seen in all the patients. Previous study by Kahrilas PJ et al, inferred that heart burn was present in nearly all GERD patients in their study and regurgitation was found in 80% of GERD patients, in contradiction to the results of our present study.…”
Section: Discussioncontrasting
confidence: 52%